Food allergens: threshold levels and methodologies for risk management - E. V. Kryuchenko; Yu. A. Kuzlyakina; I. M. Chernukha; V. S. Zamula (Пищевые системы)
Food allergies and allergen management are important problems of the public health and food industry. The idea of determining allergen concentrations in food ingredients and food products that are capable of causing severe allergic reactions is of great interest for regulatory bodies as well as consumer associations and the industry all over the world. In this connection, scientists proposed different approaches to determining the basis for assessment of severity of risks of food allergens for health of patients suffering from food allergy similar to methods of risk assessment for other hazards associated with food products (for example, chemical, microbiological). To assess risk of allergens, three different approaches were proposed: i) traditional risk assessment using the no observed adverse effect level (NOAEL)) and uncertainty factors; (ii) approach based on the benchmark dose (BMD)) and margin of exposure (MoE)); and (iii) probability models. These approaches can be used in risk management in food production and in the development of warning marking about the presence of allergens. The reliability of risk assessment will depend on a type, quality and quantity of data used for determining both population threshold levels (or threshold distributions) and an impact of an allergenic product/ingredient on a particular individual.